National surveillance data analysis of COVID-19 vaccine uptake in England by women of reproductive age - Magee, Laura A.; Molteni, Erika; Bowyer, Vicky; Bone, Jeffrey N.; Boulding, Harriet; Khalil, Asma; Mistry, Hiten D.; Poston, Lucilla; Silverio, Sergio A.; Wolfe, Ingrid; Duncan, Emma L.; von Dadelszen, Peter (Nature communications, 2023)
Women of reproductive age are a group of particular concern with regards to vaccine uptake, related to their unique considerations of menstruation, fertility, and pregnancy. To obtain vaccine uptake data specific to this group, we obtained vaccine surveillance data from the Office for National Statistics, linked with COVID-19 vaccination status from the National Immunisation Management Service, England, from 8 Dec 2020 to 15 Feb 2021; data from 13,128,525 such women at population-level, were clustered by age (18–29, 30–39, and 40–49 years), self-defined ethnicity (19 UK government categories), and index of multiple deprivation (IMD, geographically-defined IMD quintiles). Here we show that among women of reproductive age, older age, White ethnicity and being in the least-deprived index of multiple deprivation are each independently associated with higher vaccine uptake, for first and second doses; however, ethnicity exerts the strongest influence (and IMD the weakest). These findings should inform future vaccination public messaging and policy. Women of reproductive age may have specific concerns relating to perceived impacts on fertility and menstrual cycles that make them hesitant to receive COVID-19 vaccination. In this study, the authors explore COVID-19 vaccine uptake rates in women of reproductive age using linked data for ~13 million women in England.